Real-World Insights From Türkiye: Biologic DMARDs Usage in Spondyloarthritis Patients With Chronic Kidney Disease - Gokten, Dilara Bulut; Tezcan, Mehmet Engin; Yagiz, Burcu; Erden, Abdulsamet; Kimyon, Gezmis; Yasar Bilge, Nazife Sule; Mercan, Ridvan (Wiley, 2025)
AimThe objective was to evaluate biologic disease-modifying antirheumatic drugs (DMARDs) and their side effects that hindered the continuation of treatment in a patient population diagnosed with spondyloarthritis (SpA) with a glomerular filtration rate (GFR) <= 60 mL/min, and to compare these side effects between patients with chronic kidney disease (CKD) and those without.MethodsThis multicenter, observational cohort study utilized data from the TReasure database, which records SpA patients in a web-based system across T & uuml;rkiye. A total of 6052 patients being included. SpA patients were categorized into two main groups: non-CKD patients and CKD patients. The clinical characteristics, disease activity, treatment options, drug retention rates, reasons for drug discontinuation, and types of adverse effects were compared between the groups.ResultsBiologics prescription pattern varied between CKD and non-CKD patients. Etanercept was prescribed more frequently (53.1%) in CKD patients. Regarding the number of side effects and drug discontinuations in CKD patients, no statistically significant differences were found between the non-CKD and CKD groups for any of the bDMARDs (adalimumab, etanercept, golimumab, infliximab, ustekinumab, secukinumab, and certolizumab). No statistically significant differences were observed in the duration of drug retention based on CKD status for bDMARDs.ConclusionThis study offers preliminary evidence supporting the effective and safe use of bDMARDs in patients with SpA and CKD.
Keywords: adverse event; biologic DMARDs; chronic kidney disease; safe use; spondylarthritis